Toward the Year 2000 / Work in Progress - Bell Daniel (Houghton Mifflin Company, 1968)
Preface, The Year 2000 - The Trajectory of an Idea, Baselines for the Future, Alternative Futures, The Needs for Models, Some Specific Problems, Can Social Prediction Be Evaluated?, Forecasting and Technological Forecasting, Modernizing Urban Development, The Need for a Political New Theory, Educational and Scientific Institutions, Biological Man and the Year 2000, Religion and Mysticism and the Institutional Church, Memorandum on Youth, The Problems of Privacy in the Year 2000, Some Psychological Perspectives on the Year 2000, Notes on Meritocracy, Violence, Communication, The Nature and Limitations of Forecasting, The Need for Normative Statements, The Working Parties, Coda: Work in Further Progress, Notes on Contributors, Index.